Physicochemical soil quality of silvopastoral system for forest resource management in Canoa, San Vicente, Ecuador - Cevallos Vera, Arelis Stefania (2026)
This article evaluates the physicochemical quality of silvopastoral soils at “La Florida” farm, located in Canoa parish, Ecuador, with the aim of proposing a sustainable forest management model. Soil analyses showed bulk density between 0.91 and 0.93 g/cm³ and porosity above 60 %, which are optimal conditions for root development. The pH ranged from 6.6 to 7.5, indicating slightly acidic to neutral soils, while organic matter reached up to 4.9 %. Organic carbon content varied from 1.74 to 2.90 %, and total nitrogen from 0.15 to 0.25 %, with a C/N ratio of 11.5, suggesting rapid mineralization. Areas with lower fertility and reduced phosphorus availability (27 mEq/ml) were identified as degraded zones mainly due to overgrazing. The forest inventory highlighted species with significant biomass and carbon storage contributions, such as Samanea saman and Prosopis juliflora. The proposed model integrates agroforestry techniques, crop rotation, controlled grazing, climate monitoring, and mechanisms like REDD+ to conserve biodiversity, improve agricultural productivity, and mitigate climate change.